Effectiveness of Mancozeb and Benalaxyl Against Purple Blotch Disease Caused by Alternaria porri Howard (Dothideomycetes: Pleosporaceae) In Shallot (Allium ascalonicum L.) - Liana Juvita; Anton Muhibuddin (University of Brawijaya, 2022)
The common control of purple blotch disease of shallot cause by Alternaria porri is using fungicide. Application of mancozeb and benalaxyl was reported effectively suppress the intensity of purple blotch disease. The aim of this study was to evaluate the effective doses of mancozeb and benalaxyl fungicide against purple blotch disease of shallot in vivo and in vitro. A Randomize Block Design (RBD) with 5 treatments and 5 replicates were used in in vivo experiments and A Randomize Complete Design (RCD) with 6 treatments and 3 replicates were used in in vitro experiments. Disease intensity, fungicide efficacy rate (ER), and production were evaluated in vivo experiment. The growth of A. porri colony, fungicide relative inhibitions rate, compounds fungicide activity character, the biomass of mycelium on potato dextrose agar (PDA) and potato dextrose broth (PDB) were evaluated during in vitro experiment. The result showed that the highest of mixtured fungicide efficacy (90.15%) was found on the highest treatments (2.0 g/l) of fungicides application. It was also found that all fungicides suppressed growth of colony and biomass of A. porri mycelium on PDA+PDB media. The lowest growth of colony, biomass of A. porri mycelium was found on PDA+PDB media and the highest relative inhibition rate was showed on mixtured of mancozeb+benalaxyl treatment. The fungicide activity character which evaluated from co-toxicity value, indicated that there was a sinergistic between mancozeb and benalaxyl (NK ≥ 1) to inhibit growth of A. porri.